Solve the equations: 4 - (2x-3) = 3(x+2) + 4 and 3 - (3x-1) = 2(x+3) - 1

1 Answer | Add Yours

Top Answer

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The following equations have to be solved for x:

4 - (2x-3) = 3(x+2) + 4

=> 4 - 2x + 3 = 3x + 6 + 4

=> -2x + 7 = 3x + 10

=> 5x = -3

=> x = -3/5

And 3 - (3x - 1) = 2(x+3) - 1

=> 3 - 3x + 1 = 2x + 6 - 1

=> 4 - 3x = 2x + 5

=> 5x = -1

=> x = -1/5

The solution of 4 - (2x-3) = 3(x+2) + 4 is x = -3/5 and the solution of 3 - (3x - 1) = 2(x+3) - 1 is x = -1/5

We’ve answered 318,982 questions. We can answer yours, too.

Ask a question